Analysis of the Relationship Between the Implementation of Patient Safety Culture and Staff Perceptions of the Level of Patient Safety at Cikarang Community Health Center Using the Hospital Survey on Patient Safety Culture (HSOPSC) - Setianingsih, Lyliana Endang; Ice Marini; Emmelia Kristina Hutagaol; Afif Wahyudi Hidayat; Anom Dwi Prakoso (Jurnal EduHealth, 2023)
Implementing patient safety at Community Health Center is one of the main priorities in providing high quality health services to patients. As a part from carrying out its function as a public health service, a Community Health Center must also pay attention to continuously improving patient safety, in achieving universal and sustainable health coverage. The aim of this research is to gain an understanding of the influence of patient safety culture on staff perceptions of patient safety level in Cikarang Community Center. This design of this research is a quantitative analysis design with a cross sectional study approach, using observational research method. The subjects of this research are staff (including medical health workers and non-medical health workers) at the Cikarang Community Health Center, which consists of 57 personels, and the technique used is total sampling method. The majority of the staff in Cikarang Community Health Center perceive the patient safety level to be excellent (68,4%). The factors that have significant relationship with the patient safety perception are teamwork (p-value = 0,023), management support (p-value = 0,042), overall perception of patient safety (p-value = 0,029), feedback and communication about errors (p-value = 0,034), and incident reporting frequency (p-value = 0,012). The factors that influence staff perception on patient safety level are incident reporting frequency (OR = 7,738), teamwork (OR = 2,554), supervisor support (OR = 1,287) and management support (OR = 2,102), while the factor that are less likely to influence staff perception on patient safety level are organizational learning (OR = 0,681), feedback and communication about errors (OR = 0147), and communicative openness (OR = 0,550). The improvement of patient safety culture in Cikarang Community Health Center can be done by increasing in im plementation of incident reporting frequency, teamwork, supervisor support and management support.